A Peep Through The Real Insinuated Connotation Of Sepedi Proverbs About Women From Marema-Ka-Dika: Rakoma 1995 (Journal of Namibian Studies : History Politics Culture, 2023)
In the Pedi language, like many other African languages, proverbs about women tend to erode their precious beautiful, and strong character, as compared to those proverbs about men. Proverbs about women are always meant to demean, belittle and defame them at all costs; they are associated with ‘ditṡhwene’ (Baboons). Women are always blamed for all wrongdoings, allocated hard labor, and over and above obliged to bear as many children as possible. It should always be remembered that in African culture a woman is at least offered minimal respect if she procreates male children. South Africa is among the countries that still uphold certain traditions and customs that overlook the discrimination that results from treating women as subordinate to men (Magezi, Baloyi, Matsobane, and Manala, 2019:3). This undermines females in a patriarchal society. Mbiti (1969:142) notes: “If the first wife has no children or only daughters, it is likely that her husband will find another wife”. This shows that the lack of male children in the family is considered a serious problem. The main objective of this study was to identify all so-called illicit proverbs about women, provide analysis and interpretation and prognosticate the motive behind the formulation of such proverbs.